13a+2=6(a-2)

Simple and best practice solution for 13a+2=6(a-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13a+2=6(a-2) equation:


Simplifying
13a + 2 = 6(a + -2)

Reorder the terms:
2 + 13a = 6(a + -2)

Reorder the terms:
2 + 13a = 6(-2 + a)
2 + 13a = (-2 * 6 + a * 6)
2 + 13a = (-12 + 6a)

Solving
2 + 13a = -12 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
2 + 13a + -6a = -12 + 6a + -6a

Combine like terms: 13a + -6a = 7a
2 + 7a = -12 + 6a + -6a

Combine like terms: 6a + -6a = 0
2 + 7a = -12 + 0
2 + 7a = -12

Add '-2' to each side of the equation.
2 + -2 + 7a = -12 + -2

Combine like terms: 2 + -2 = 0
0 + 7a = -12 + -2
7a = -12 + -2

Combine like terms: -12 + -2 = -14
7a = -14

Divide each side by '7'.
a = -2

Simplifying
a = -2

See similar equations:

| 306/6 | | b=3(h-1) | | 5/3/3/5 | | 6(x-3)/4=3(x+8)/13 | | x-2=59 | | -10-4x=2-x | | 18/30=n/10 | | -10m+8=-122 | | 11x+3-3x=-4x-33 | | 3[x-4]=48 | | 6(x-2)/2=3(x+3)/6 | | 6+5x=8x-6 | | (-3x)+5=7 | | 10+2n=34 | | -6+14=x | | (2x/5)+(2x/3)=16 | | 1m+7=3+3m | | x-31=-24 | | x-88=-69 | | 3.6=6x | | 1/2(x+3/4)=x-13/8 | | 3p-6p=-7p+20 | | 2/3=14 | | n/30=5/6 | | 3x^2+8x=-13 | | 3x+26=6x+5 | | 14x-160=20x-10 | | (-37)+x=5 | | N-12n-24=101 | | 1m+9=12m-8m+21 | | 3x+26+6x+5=180 | | 4(y+5)+y=3(y+4)+6 |

Equations solver categories